A vapochromic dye/graphene coated long-period fiber grating for benzene vapor sensing. (19th July 2022) - Dong, Lianghai; Zhao, Ke; Wu, Jieyun; Deng, Guowei; Tang, Chunlan; Zhang, Chun; Xu, Huajun; Wang, Qihui; Chen, Kaixin; Chiang, Kin Seng
Abstract : A vapochromic dye was synthesized and coated on a long-period fiber grating sensor for specific benzene vapor sensing with an ultra-large dynamic range. Abstract : The exploration of new materials and devices for the identification and detection of toxic and carcinogenic benzene vapor is considerably significant due to its severe toxicity and carcinogenicity for human health. Herein the material and device engineering for benzene sensing was systematically performed. A novel vapochromic dye IDTC1 with acceptor-π-acceptor was facilely synthesized and the vapochromism in the UV-vis absorption spectrum was studied. The spin-coated thin film IDTC1 showed a specific and reversible wavelength blue-shift by 44 nm in benzene vapor, indicating the benzene-induced vapochromic effect. For the quantitative detection of benzene vapor, a long-period fiber grating (LPFG) sensor coated with graphene/IDTC1 as sensitive fiber cladding was designed and fabricated. The benzene-induced vapochromism resulted in the refractive index change of the IDTC1 film on the fiber, leading to the resonant central wavelength change of LPFG. The LPFG showed a wide dynamic range (20 ppm to 23 000 ppm) and high sensitivity (0.36 pm ppm −1 ) of quantitative benzene sensing. Density functional theory calculation analysis indicated that the specific benzene-induced vapochromism might have resulted from the π–π stacking of aromatic benzenes and the steric hindrance effect on the conjugate electron-bridge. Our innovative study in material and device engineering implied the promising application of vapochromic dye IDTC1 for volatile organic compound sensing.